Implementation of Managerial Supervision of Madrasah Heads - Zamrodatin, Mamik; Darim, Abu; Ardianto, Ardianto; Rofiq, Muhammad Husnur (Chalim Journal of Teaching and Learning, 2023)
This study used a qualitative approach to the type of case study. To determine the data source, purposive sampling was used with the consideration that the selected subjects and informants were people who were able to provide as much information as possible regarding the research focus. Furthermore, to select and determine the informants in this study, the snowball sampling technique was used. While collecting data in this study using three techniques, namely: observation, interviews, and documentation. Data analysis was carried out using data reduction, data display, and conclusion drawing/verification. The results of research while in the field are as follows Kamad RA Darussalam Bojonegoro has a very convincing ability in preparing madrasa planning for various levels of planning. 1) Kamad RA Darussalam Bojonegoro can be quite convincing in leading madrasas in the context of optimally utilizing madrasah resources. 2) Kamad RA Darussalam Bojonegoro is capable of being very convincing in creating a conducive and innovative school culture and climate for student learning.